In vitro and in silico studies of Lawsone on inflammation-induced skin cells for development of skin anti-inflammatory treatment - Abdullah, Shazleen Sofea; Mohammad Latif, Muhammad Alif; Md Tohid, Siti Farah (Malaysian Society of Applied Biology, 2024)
Lawsone, an active phytoconstituent of Lawsonia inermis sp., is proposed as a safer alternative for the current skin anti-inflammatory treatments that are mainly steroidal with unwanted side effects which does not conform to the concept of halalan toyyiban in medicine. This study aims to investigate the inhibitory mechanism of lawsone on pro-inflammatory cytokine, TNF (tumour necrosis factor)-α through in silico and in vitro methods. The inhibitory mechanism of lawsone were investigated via molecular docking and molecular dynamics which were performed via AutoDock Vina and GROMACS softwares, respectively. The results were then analysed via PyMol, Proteins Plus, RMSD and RMSF graphs. Subsequently, cytotoxicity of lawsone towards A431 skin epidermoid and 3T3 fibroblast cells, was determined via MTT assay. Lawsone was further tested on A431 cells stimulated with ethanol (200 mM) or hydrogen peroxide (250 µM) for 24 hours (acute) and 48 hours (chronic) to induce pro-inflammatory cytokine (TNF-α) release. Cell viabilities were determined via MTT assay and expression of TNF-α were measured via ELISA. In silico works predicted lawsone’s ability to bind to TNF-α with good binding affinity without disruption to the protein’s structure stability.Lawsone is proven to be safe towards non-pathological cells. Lawsone exhibited significant anti-inflammatory effect on inflammation induced A431 epidermoid cells. ELISA results were not as expected as compared to previous in silico study, but an anti-inflammatory pattern can be observed in the chronic ethanol-induced treatment groups. In conclusion, lawsone is shown to have potential to be developed as a halalan- toyyiban alternative for skin anti-inflammatory treatment.